Knowledge of chronic kidney disease management among primary healthcare doctors: a cross-sectional study - Kim Yen, Lee; Yaacob, Lili Husniati; Ismail, Shaiful Bahari (Faculty of Medicine, 2026)
The prevalence of chronic kidney disease (CKD) is increasing worldwide including in Malaysia. Primary healthcare professionals are required to have sufficient knowledge in all aspects of CKD management. The study aims to determine the level of knowledge on chronic kidney disease and management, its associated factors, and to describe the practice of chronic kidney disease management among public primary healthcare providers in Kelantan. Methods: This was a cross-sectional study using an online self-administered questionnaire involving purposively sampled medical officers working at the health clinics in the Ministry of Health. The questionnaire assessed knowledge of CKD definition, risk factors, complications, investigations, and management. Descriptive statistics and multivariate analysis were used to determine factors associated with knowledge level. Results: One hundred seventy-nine primary healthcare providers in Kelantan participated in this study. The mean score for knowledge among primary healthcare providers was 71.6% (SD= 13.5). Most participants were able to identify the risk factors of CKD correctly. Previous exposure to CKD management training (p= 0.004; 95% CI: -9.49, -1.79%) and use of clinical practice guidelines (p< 0.001; 95% CI: -13.91, -4.17%) were significantly associated with knowledge. Some practices among the participants were discordant with the guidelines. More than three- quarters (n=137) of participants used serum creatinine as the initial screening test for CKD, whereas only 47.5% (n=85) screened for anaemia among CKD patients. Conclusion: Previous exposure to training and usage of guidelines were significant associated factors for the level of knowledge. Educational activities and the availability of guidelines in clinical practice are important to improve the quality of care among healthcare professionals.